Sistem Pendukung Keputusan Pemberian Beasiswa Kepada Peserta Didik Baru Menggunakan Metode TOPSIS, WP, dan SAW - Atina Fahma Rosyada; Ikhwan Sukirman; Muhammad Afrizal Nur; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The management of educational institutions faces challenges due to the large number of scholarship applications to be able to make the right, effective and efficient decisions when handling scholarship recipient data that is truly appropriate for them. The standards applied in this system change depending on the type of scholarship the organization is offering. The TOPSIS, WP, and SAW methods will be used to calculate the applicant's value data by determining the applicant's distance from the positive and negative ideal solutions. The top applicant in this method will be the applicant with the highest v score. The results of selecting the case examples show that the system calculations produce the correct conclusions.